MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN LAYANAN PENDIDIKAN DI MA’HAD AL-JAMI’AH UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI - Chaniago, Fransisko (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2020)
The purpose of the research are to find out the inhibiting and supporting factors and efforts was done by the leadership in improving Education Services in Ma'had Al-jami'ah The State Islamic University of Sulthan Thaha Saifuddin Jambi that still unoptimal. This research used qualitative approach which is a method that is used to find the broadest knowledge of the research objects at the time the research was conducted. The approach used in this research is descriptive research approach. The findings and analysis research are, namely 1) Educational services at Ma'had Al-jami'ah The State Islamic University of Sulthan Thaha Saifuddin Jambi include services provided through Academic division, Tahfiz division, Religious division, and Students division. 2) The inhibiting factors are facilities and infrastructure, those are still inadequate in improving educational services, scheduling of College learning and Ma’had learning often collide, workloads are not balanced with existing employees, and the lack budget for improving the employee competency. And supporting factors of human resources recruited through alumni of Boarding School, employee dedication on their work, facilities and infrastructure. 3) The Leadership Efforts in improving education services, namely by increasing discipline, conducting training, proposing the addition of employees who are not balanced with their workload, conducting work evaluation meetings, discussing intensively with the rector regarding facilities and infrastructure, having an audience with the college authorities about learning schedule.